'Horizontal effect' of the Hong Kong Basic Law. (June 2016) - Liu, Hin Ting; Chan, Joshua
One area of Hong Kong law which has received surprisingly little attention is how far its human rights provisions reach into the private sphere. This issue is commonly known as 'horizontal effect'. It will be argued that in the Hong Kong context, courts are under an obligation to develop the common law with a view to achieving maximum consistency with the Hong Kong Basic Law, even when a purely private dispute is involved. As such, judges should not feel constrained by legislative inaction, but should take the initiative to fill perceived gaps in the common law in order to fulfil their obligation to adjudicate in accordance with the Basic Law. In the final analysis, it is suggested that this obligation may even necessitate the creation of a new cause of action or require the judge to rule inconsistently with a superior court's decision.